2009
DOI: 10.5897/ajb09.360
|View full text |Cite
|
Sign up to set email alerts
|

The genus Calvatia (Gasteromycetes, Lycoperdaceae): A review of its ethnomycology and biotechnological potential

Abstract: Several members of the fungal puffball genus Calvatia Fr. have found widespread use amongst various cultures world-wide, especially as sources of food and/or traditional medicine. Hitherto the biotechnological potential of only a handful of Calvatia species, namely C. cyathiformis, C. craniiformis, C. excipuliformis, C. gigantea and C. utriformis has been investigated. However, despite promising results, information regarding the biotechnological potential of the rest of the genus, in particular the African sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…All Calvatia species are edible (Morris, 1987), but only in the immature state before the commencement of spores maturation and while the gleba is still firm and white (Gray, 1973;Grigson, 1978). Edibility of Calvatia cyathiformis and Calvatia fragilis is supported by many researchers (Christensen, 1955;Atkinson, 1961;Krieger, 1967;Purkayastha and Chandra, 1985;Coetzee and Wyk, 2009). Edibility of above species was reported by the interaction with tribal people of Korku and Pardhi community and confirmed myself by eating the dish.…”
Section: Edibilitymentioning
confidence: 62%
“…All Calvatia species are edible (Morris, 1987), but only in the immature state before the commencement of spores maturation and while the gleba is still firm and white (Gray, 1973;Grigson, 1978). Edibility of Calvatia cyathiformis and Calvatia fragilis is supported by many researchers (Christensen, 1955;Atkinson, 1961;Krieger, 1967;Purkayastha and Chandra, 1985;Coetzee and Wyk, 2009). Edibility of above species was reported by the interaction with tribal people of Korku and Pardhi community and confirmed myself by eating the dish.…”
Section: Edibilitymentioning
confidence: 62%
“…All Calvatia species are edible (Morris, 1987), but only in the immature state before the commencement of spores maturation and while the gleba is still firm and white (Hedawoo, 2020). Edibility of Calvatia cyathiformis, Calvatia fragilis, Lycoperdon perlatum is supported by many researchers e.g., (Coetzee & Wyk, 2009;Chakraborty et al, 2012;Verma et al, 2018;Hedawoo, 2020). These species are referred to as the ''poor man's sweetbread'' due to their texture and flavour.…”
Section: Resultsmentioning
confidence: 99%
“…A portion of the basidiomycetes corresponds to gasteroid fungi, widely distributed in the tropics (Mueller et al, 2007), mainly in Brazil, where the diversity of the group increases every year (Accioly et al, 2019;Assis et al, 2022;Ferreira-Sá et al, 2021;Freitas et al, 2023;Santana & Couceiro, 2023). Studies with this group revealed the production of important substances with proven biological activity (Liu & Zhang, 2004;Dore et al, 2007;Coetze and Van Wyk, 2009), but there is a study gap regarding the discoloration of synthetic dyes. The genera Cyathus Haller and Geastrum Pers., common taxa in forests are known to be producers of bioactive compounds useful for bioremediation and discoloration of some synthetic dyes (Vasdev and Kuhad, 1994;Vasdev et al, 1995;Mishra and Bisaria, 2006;Santana et al, 2016), but there is no information on these genera regarding the discoloration of trypan blue.…”
Section: Trypan Blue Dye Discoloration In Solid Culture Mediummentioning
confidence: 99%